EFFECT OF COMPRESSIVE STRENGTH AND SLUMP VALUE OF CONCRETE USING LIME POWDER (CaCO3) AS A PARTIAL REPLACEMENT OF CEMENT - Sultan, Muhammad Aswar; Yusuf, Jasman; Hamsyah, Hamsyah (STABILITA || Jurnal Ilmiah Teknik Sipil, 2023)
Lime powder is the result of burning with a temperature of  900-1500 °C from limestone and then immediately splashed with air when conditions are hot. Limestone is a material derived from white and fine sedimentary rock which is mainly composed of the mineral calcium. This study aims to determine the effect of strong compressive strength and slump value on the partial replacement of cement with lime powder. This study used an experimental method by comparing the compressive strength and slump value of concrete mixed with lime powder. This research was conducted for 2 months. The results showed that variations of 0%, 1% and 5% lime powder met the desired slump requirements, which were between 50 – 125 mm, while the 10% variation did not meet the requirements. Testing the compressive strength of concrete at 28 days with a 0% variation of 25.29 MPa, a 1% variation of 25.38 MPa, a 5% variation of 25.57 MPa and a 10% variation of 20.67 MPa. So it can be concluded that lime powder can be used as a partial replacement for cement with variations of 1% and 5% because the slump value meets the requirements and the resulting compressive strength has increased from normal concrete.